Sri Lanka : Second Review under the Extended Arrangement under the Extended Fund Facility, Request for Waivers of Applicability and Nonobservance of Performance Criterion, and Request for Modification of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Sri Lanka's Second Review under the Extended Arrangement under the Extended Fund Facility, Request for Waivers of Applicability and Nonobservance of Performance Criterion (PC), and Request for Modification of PCs. The authorities remain committed to the economic reform program and undertook meaningful corrective actions where targets were missed. As a prior action, the new Inland Revenue Act will be submitted to Parliament. The authorities have also strengthened tax administration and are conducting a diagnostic review of the value-added tax. The reform momentum should strengthen further, building on the progress made so far.